1997
DOI: 10.2355/isijinternational.37.240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu and Other Tramp Elements on Steel Properties. Effects of 0.4% Si and 0.02% P Additions on Surface Hot Shortness in 0.1%C-0.5%Mn Steels Containing 0.5% Cu.

Abstract: The objective of this paper is to examine the effects of Si

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…On the other hand, Seo et al 5) found that the susceptibility to the surface hot shortness depended on the strain rate and showed the maximum at around 1 × 10 −1 s −1 . Figure 17 shows the effect of strain rate on stress-strain curves of specimens implanted with a Cu-20%Sn rod into 0.1%C-0.5%Mn-0.5%Cu steel.…”
Section: Effects Of Atmosphere Of Heating Furnace and Deformation Ratementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Seo et al 5) found that the susceptibility to the surface hot shortness depended on the strain rate and showed the maximum at around 1 × 10 −1 s −1 . Figure 17 shows the effect of strain rate on stress-strain curves of specimens implanted with a Cu-20%Sn rod into 0.1%C-0.5%Mn-0.5%Cu steel.…”
Section: Effects Of Atmosphere Of Heating Furnace and Deformation Ratementioning
confidence: 99%
“…4, E p and E p at 1473 K are found to be maller than those at 1373 K. As for E e the effect of heating temperature is opposite and the reason for this has been mentioned before (3.2). It has been generally observed that the surface hot shortness tends to occur most severely around 1373 K. 2,5,12) The reasons for this result are conceived to be as follows. At higher temperatures, internal oxidation and grain boundary oxidation tend to occur and occlusion of the Cu-enriched phase into scale are accelerated.…”
Section: Effects Of Heating Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…5) The silicon addition also decreases the amount of precipitated copper by the occlusion of copper in the oxide scale and reduces the susceptibility of hot shortness at 1 373 K, where the liquid Fe-Si oxide does not formed. 6) It is reported that the addition of phosphorus, carbon, and boron are favourable elements for hot shortness. These elements are thought to change the distribution of liquid copper in the scale, steel grain size, and the toughness of steel grain boundary for the crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The addition of silicon also has been beneficial to this problem. 5,6) The addition of silicon reduces the susceptibility of hot shortness at more than 1 473 K, since the liquid precipitation of copper is trapped in the liquid oxide formed by silicon. 5) The silicon addition also decreases the amount of precipitated copper by the occlusion of copper in the oxide scale and reduces the susceptibility of hot shortness at 1 373 K, where the liquid Fe-Si oxide does not formed.…”
Section: Introductionmentioning
confidence: 99%